Renal replacement therapy neutralizes elevated MIF levels in septic shock. Issue 1 (December 2016) - Pohl, Julia; Papathanasiou, Maria; Heisler, Martin; Stock, Pia; Kelm, Malte; Hendgen-Cotta, Ulrike; Rassaf, Tienush; Luedike, Peter
Abstract Background Macrophage migration inhibitory factor (MIF) is known to amplify the immune response in septic animal models. Few clinical data support this pro-inflammatory role in septic patients. Renal replacement therapy (RRT) as adjuvants in the complex therapy of sepsis has been proposed as a possible approach to eliminate elevated circulating cytokines. Since recent data suggest that MIF can be effectively removed from the circulating blood pool in patients with chronic kidney disease, we here aimed to investigate whether RRT in septic shock can lower plasma levels of this pro-inflammatory cytokine in septic shock patients. Methods An observational single-center study on an internist intensive care unit (ICU) was conducted. MIF plasma levels and mortality ofn  = 25 patients with septic shock were assessed with a previously validated method for reliable MIF values. The effect of continuous renal replacement therapy (CRRT) on daily MIF levels and mortality was assessed by comparing patients with and without need for CRRT due to acute kidney injury (AKI). Results MIF plasma levels in patients undergoing CRRT due to septic AKI were steadily decreased compared to those from patients without CRRT hinting at a MIF removal by hemodialysis. MIF release during ICU stay as assessed by MIFAUC was lower in patients undergoing CRRT, and Kaplan-Meier analysis revealed a distinctly lower mortality in patients undergoing CRRT. Analysis of daily MIF levels showed that patients who did not survive septic shock exhibited steadily higher MIF plasma levels and higher MIFAUC compared to those surviving sepsis. Low MIF levels were closely associated with improved survival. Conclusions This is the first study investigating the effect of efficient MIF removal from the plasma pool of patients with septic shock. Reduction of high circulating MIF by CRRT therapy was accompanied by improved survival. Thus, targeted removal of MIF from the circulating blood pool might be a promising approach to reduce mortality in severe sepsis.